2019
DOI: 10.24251/hicss.2019.240
|View full text |Cite
|
Sign up to set email alerts
|

Personalize Wayfinding Information for Fire Responders based on Virtual Reality Training Data

Abstract: Modern buildings with increasing complexity (e.g., more square feet, complicated indoor routes) can cause serious difficulties for first responders in emergency wayfinding. While real-time data collection and information analytics become easier in indoor wayfinding, a new challenge has arisen: cognitive overload due to information redundancy. Standardized and universal spatial information systems are still widely used, ignoring first responders' individual difference in information intake. This paper proposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Wayfinding has been used extensively in evacuation and navigation experiments, since it creates affordances by prompting human actions [26,27]. Various studies have investigated design, and implementation of navigation processes such as wayfinding cues inside the VRE for training and evacuation applications [28].…”
Section: Wayfinding In Virtual Reality Training Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wayfinding has been used extensively in evacuation and navigation experiments, since it creates affordances by prompting human actions [26,27]. Various studies have investigated design, and implementation of navigation processes such as wayfinding cues inside the VRE for training and evacuation applications [28].…”
Section: Wayfinding In Virtual Reality Training Simulationsmentioning
confidence: 99%
“…In the past, wayfinding studies have been conducted in indoor environments [31,33] and mostly for fire [27,34,35], underground rock-related hazards safety training [33] and earthquake evacuations [10,14]. These researches have [32] suggested that further studies should be conducted to improve the evaluation process for VR evacuation trainings.…”
Section: Wayfinding In Virtual Reality Training Simulationsmentioning
confidence: 99%